Meningkatkan Aktivitas Dan Hasil Belajar Dengan Model PBL,TPS Dan NHT Di Kelas IV SDN TELUK DALAM 11 - Muhammad Rizaldi; Tika Puspita Widya Rini (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
The issue in this exploration is the absence of understudy action and learning results of 4th grade understudies at SDN Teluk Dalam 11 Banjarmasin. Through the Issue Based Learning model, Think Pair Offer, and Numbered Heads Together which are elective answers for critical thinking. The motivation behind this examination is to further develop resilience abilities and understudy acquiring results. This examination utilizes a subjective methodology with the kind of Study hall Activity Exploration (Vehicle). The subjects of this review were 4th grade understudies at SDN Teluk Dalam 11 Banjarmasin, the quantity of understudies was 7 individuals. Information examination in this study utilized distinct investigation strategies converted into tables, diagrams and translations with rates. The outcomes showed that educator movement at meeting IV got a score of 32. Understudy movement at IV got a level of 93%. The understudies' resilience abilities at meeting IV got an old style level of 94%. In view of these discoveries it tends to be presumed that this model can increment understudy movement and understudy learning results.